Digital Transformation, Resilience, and Entrepreneurial Empowerment in Community-Based Tourism: A Systematic Literature Review - Utomo, Sherly Rakasiwi Putri (Integrasi Sains Media, 2026)
Community-based tourism (CBT) is transitioning from passive local participation to active entrepreneurial empowerment amidst global crises and rapid digitalization. To address the fragmented understanding of this paradigm shift, this Systematic Literature Review (SLR) adheres to PRISMA 2020 guidelines, synthesizing 40 high-impact Scopus articles published between 2016 and 2026. This study explores the critical intersection of digital transformation, socio-economic resilience, and entrepreneurial empowerment within rural destinations. The findings reveal a dual-edged nature of digitalization: while e-tourism platforms empower micro, small, and medium enterprises (MSMEs) by bypassing traditional intermediaries, they risk exacerbating the local digital divide without robust grassroots capacity building. Furthermore, the synthesis demonstrates that post-crisis destination resilience relies heavily on diversifying livelihood portfolios and leveraging cultural heritage rather than mere financial reconstruction. Ultimately, this review proposes the Regenerative Smart CBT Framework, establishing that technological adoption and sustainable leadership must be directly mediated by localized entrepreneurship. This structural mediation is essential to evolve CBT from a basic conservation strategy into a proactive engine for ecological regeneration and long-term socio-economic resilience.